Pemertahanan Bahasa Mandar oleh Suku Mandar yang Berdomisili di Kota Makassar Sulawesi Selatan - Nurul Al Fatana; Ramly Ramly; Azis Azis (Indonesian Journal of Social and Educational Studies, 2021)
This study aims to describe:(1) the pattern of maintaining the Mandar language by the Mandar tribe domiciled in Makassar City, South Sulawesi, (2) describing the supporting factors for the maintenance of the Mandar language by the Mandar tribe living in Makassar City, South Sulawesi. This type of research is descriptive qualitative research using an ethnographic approach which is also supported by a sociolinguistic approach. This research was conducted in one of the domicile places of the Mandar tribe, namely Toddoppuli Raya, precisely in Toddopuli RW 006 RT 002 Borong Village, Manggala District, Makassar City, South Sulawesi. Data collection techniques in this study were interview techniques, questionnaires and recording protocols. Data analysis techniques were carried out by processing data related to data collection, data reduction, and drawing conclusions.The results of the study indicate the patterns and factors that support the maintenance of the Mandar language by the Mandar tribe who live in Makassar, South Sulawesi. The pattern of maintaining the Mandar language by the Mandar tribe who lives in Makassar, South Sulawesi, which was found to consist of two domains, namely: (1) family with husband-wife pattern → BM 57.2%, BI 14.3%, mixed BM, BI 28 ,6% BM persisted, father-child → BM 57.2%, mixed BM, BI 42.9% BM persisted, father-parents → BM 85.8%, mixed BM, BI 14.3% BM persisted, Grandpa /Grandmother→BM 85.8%, mixed BM, BI 14.3% BM persisted. (2) the realm of neighborhood/neighborhood patterned Neighborhood/neighborhood→BI 42.9%, mixed BM, BI 57.2%, BM persisted. The supporting factors that influence the maintenance of the Mandar language by the Mandar tribe who live in the city of Makassar, South Sulawesi are several factors, namely: (1) living environment, (2) loyalty, (3) language pride, (4) awareness of language norms.